In Situ ‘Trans-Metal Trapping’: An Efficient Way to Extend the Scope of Aromatic Deprotometalation - Brikci-Nigassa, Nahida Mokhtari; Bentabed-Ababsa, Ghenia; Erb, William; Mongin, Florence (Synthesis, 2018)
Deprotometalation is an efficient method to functionalize regioselectively aromatic compounds including heterocycles. This short review shows how it is possible to intercept aryllithiums (and other polar arylmetals) as soon as they are formed by in situ ‘trans-metal trapping’. The approach avoids long contact between aryllithiums and sensitive substrates. In addition, it allows less activated substrates to be deprotonated by non-nucleophilic lithium amides. While using chlorosilanes and borates still arouses the interest of chemists, more recently, methods based on zinc, aluminum and gallium have appeared, enabling this chemistry to grow dramatically.1 Introduction2 Silicon-Based In Situ Traps3 Boron-Based In Situ Traps4 Zinc-Based In Situ Traps5 Aluminum- and Gallium-Based In Situ Traps6 Other In Situ Traps7 Continuous-Flow In Situ ‘Trans-Metal Trapping’8 Conclusion
Keywords: transmetalation; in situ trap; deprotometalation; aromatic compounds; lithium amides; silicon; boron; zinc